Pengaruh Interest Coverage Ratio, Profitabilitas, Dividend Payout Ratio, dan Debt To Aset Ratio Terhadap Nilai Perusahaan - Vinka Triyuni Sarpta; Usep Syaipudin; Tri Joko Prasetyo; Rialdi Azhar (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The non-cyclical consumer sector is a stock sector issued by companies with businesses that are not affected by seasons or economic cycles in a country. The products or services sold are basic necessities that people always need, so their sales are not affected by economic conditions. The non-cyclical Consumer Sector is related to company value through various factors. Non-cyclical consumer sector companies produce or distribute anti-cyclical goods and services, which are not affected by economic growth. This need must exist and cannot be eliminated from daily use, so that this sector experiences growth in line with population growth and an increase in people's income. For companies that have been listed on the stock exchange, an increase in company value is equivalent to an increase in share price. Meanwhile, for companies that have not yet been listed on the stock exchange, the company's value will be reflected in things such as company sales, business prospects, level of risk faced, market conditions and other factors. Therefore, analysis of the factors that influence the value of banking companies is very important.